Mathematical Model of Brain Tumor With Radiotherapy Treatment - Sujitha, S.; Jayakumar, T.; Maheskumar, D.; Kaviyan, E. Vargees (Communications in Mathematics and Applications, 2023)
A model consisting of three components has been created to describe the interactions among glial cells, glioma cells, and radiotherapy treatment in tumor growth. An analytic solution of nonlinear differential equations is obtained. Stability analysis is discussed under three categories: trivial state, without any treatment, and radiotherapy treatment. In the absence of treatment, the stability analysis of the model demonstrates that a tumor would proliferate to its highest capacity. The treatment of radiotherapy could increase the effectiveness of the fight against gliomas. Moreover, numerical simulations are also provided for the proposed model. Finally, the validity of the system is examined by comparing the graphs of the analytical solution and numerical simulation.